Novel GLI3 Mutations in Chinese Patients with Non-syndromic Post-axial Polydactyly - Chen, X.; Yuan, L.; Xu, H.; Hu, P.; Yang, Y.; Guo, Y.; Guo, Z.; Deng, H. (Current Molecular Medicine, 2019)
Background: Polydactyly, characterized by supernumerary digits in the upper or lower extremities, is the most common congenital digital abnormalities. It derives from the defective patterning of anteroposterior axis of the developing limb, with various etiology and clinical heterogeneity. The patients with post-axial polydactyly type A (PAPA) have the typical symptom of a well-formed supernumerary digit outside the fifth digit. Objective: The aim of present study was to identify the causative mutations of two unrelated Han Chinese patients with non-syndromic PAPA. Methods: Two unrelated Han Chinese patients and 100 ethnicity-matched, unrelated normal controls were recruited for this study. BGISEQ-500 exome sequencing was performed in the two patients, followed by validation in the patients and 100 controls by using Sanger sequencing. Results: Two mutations in the GLI family zinc finger 3 gene (GLI3), including a frameshift mutation c.3437_3453delTCGAGCAGCCCTGCCCC (p.L1146RfsX95) and a nonsense mutation c.3997C>T (p.Q1333X), were identified in two patients but were absent in the 100 healthy controls. Conclusion: The two GLI3 mutations, p.L1146RfsX95 and p.Q1333X, may account for non-syndromic PAPA in the two patients, respectively. The findings of this study may expand the mutational spectrum of GLI3-PAPA and provide novel insights into the genetic basis of polydactyly.
Keywords: Polydactyly